Economic Retirement Age and Lifelong Learning - a theoretical model with heterogeneous labor, biased technical change and international sourcing - Thomas Gries; Stefan Jungblut; Tim Krieger; Henning Meyer (Center for Economic Studies and ifo Institute (CESifo), 2016)
The employability of an aging population in a world of continuous and biased technical change is top of the political agenda. Due to endogenous human capital depreciation the effective retirement age is often below statutory retirement age resulting in permanent non-employability of older workers. We analyze this phenomenon in a putty-putty human capital vintage model and focus on education and the speed of human capital depreciation. Introducing a two-stage education system with initial schooling and lifelong learning, not even lifelong learning turns out to be capable of aligning economic and statutory retirement. However, well designed education programs will keep more workers in highly productive activities at the end of their working life, and hence will substitute for simple social transfers, or for an early switch towards very low paid jobs.
Keywords: J26; O33; J64; 330; lifelong learning; retirement; employability; education system; heterogeneous labor; biased technical change